Censorium cinema and the open edge of mass publicity - Mazzarella, William 1969- (Duke University Press, 2013)
Performative dispensations : the elementary forms of mass publicity -- Who the hell do the censors think they are? Grounds of the censor's judgment -- We are the law! Censorship takes to the streets -- Quotidian eruptions : aesthetic distinction and the extimate squirm -- Obscene tendencies : censorship and the public punctum